2017
DOI: 10.1186/s13000-017-0645-0
|View full text |Cite
|
Sign up to set email alerts
|

ALK-positive gastric inflammatory myofibroblastic tumor in an adult with familial adenomatous polyposis and diffuse fundic polyposis

Abstract: BackgroundInflammatory myofibroblastic tumor (IMT) of the stomach is extremely rare in adults and exhibits a variable biological behavior that ranges from frequently benign lesions to more aggressive variants. Here we report a case of gastric IMT with lymph node metastasis in an adult who had undergone total colectomy for familial adenomatous polyposis (FAP).Case presentationA 37-year-old man presented gradual-onset epigastric discomfort; he had undergone total colectomy for FAP 6 years before. The upper endos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…[4] Most reported cases of primary gastric IMT are benign in nature. However, Jun Fan [5] reported the first gastric IMT case with metastasis in an adult. There has been controversy over whether IMT is an inflammation or tumor, benign or malignant, and its etiology and pathogenesis are still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Most reported cases of primary gastric IMT are benign in nature. However, Jun Fan [5] reported the first gastric IMT case with metastasis in an adult. There has been controversy over whether IMT is an inflammation or tumor, benign or malignant, and its etiology and pathogenesis are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that some cases of IMT might be associated with genetic mutation, Epstein–Barr virus (EBV) infection or immune dysregulation. [58]…”
Section: Discussionmentioning
confidence: 99%
“… LPG, SP Negative N.D 9 months None 22 Jadhav et al [ 21 ] 2017 18 M 8.6 Gastric leiomyoma, GIST susp. PR Negative N.D 5 years None 23 Ning et al [ 22 ] 2017 50 F 3.0 Ectopic pancreas ESD N.D N.D 2 years None 24 Fan et al [ 23 ] 2017 37 M 4.5 GIST susp. TG Positive < 0.4 6 months None 25 Lee et al [ 24 ] 2018 35 F 2.5 N.D PR N.D N.D 3 years None 26 Lee et al [ 24 ] 2018 39 F 2.0 N.D PR N.D N.D ...…”
Section: Discussionmentioning
confidence: 99%
“…Biological behavior has been classified as intermediate (occasional metastasis) group [7]. According to the literature, some IMT cases may be related to gene mutation, virus infection or immune system regulation [8] [9] [10] [11]. The tumor is not sensitive to radiotherapy and chemotherapy, and surgical treatment is still the main treatment.…”
Section: Discussionmentioning
confidence: 99%